Pengaruh Metode Pembelajaran dan Kesadaran Sejarah Pada Mata Pelajaran Sejarah Terhadap Hasil Belajar Sejarah Siswa di SMA Negeri I Muara Bungo/Jambi - Nanda Permana (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2017)
The aim of this research is to find out the effect of learnning method and historicalconsiousness on history studies to the result of student’s history learning in SMA I MuaraBungo/Jambi. This reseacrh is quantitative research that used experiment design treatment method bylevel 2x2. Instrument that writer used to measure the historical consiousness is questioner, andinstrument that writer used to measure the result of learning is Multiple Choice. The result ofresearch showed those (1). The result of learning history that students used CIRC were higher thanstudents in convensional learning. (2) there is interaction’s effect between the method of learning andhistorical consiousness. (3) the result of student’s history learning that use CIRC have historicalconsiousness is higher than student which use convensional learning. (4) the result of learninghistory, the students were used CIRC method have low historical consiousness lower than studentsused convensional learning which have low historical consciousness.